Analisis Yuridis Pidana Dalam Kasus Demonstrasi yang Berujung Pada Kerusuhan: Studi Tentang Implementasi Pasal 170 KUHP dan Implikasinya Terhadap Kebebasan Berbicara di Indonesia - Lufty, Arya Fajar; Panjaitan, Junifer Dame (Media Hukum Indonesia (MHI), 2025)
Democracy is a form of government in which power rests with the people. Freedom of speech and assembly are the fundamental foundations of a democratic state. In Indonesia, these rights are guaranteed by the constitution. However, in practice, demonstrations, which embody these freedoms, often end in violence and riots. Law enforcement responds by enforcing Article 170 of the Criminal Code against demonstrators deemed to be engaging in violence. This conflict between rights and public order creates a complex and compelling dilemma to analyze. This research employs a normative approach and case studies. It finds that the application of Article 170 of the Criminal Code must be selective and proportional to avoid violations of human rights and the principles of the rule of law.